Strategi Digital Perguruan Tinggi Keagamaan Buddha di Indonesia - Heriyanto Heriyanto (Jurnal Pelita Dharma, 2019)
The problem in this research is how is the digital strategy of the Buddhist Religious College (PTKB) in Indonesia. The focus of the research is directed at the digital strategy of Buddhist Religious College in Indonesia. The research objective is to describe the digital strategy of Buddhist Religious College in Indonesia. This type of research is qualitative research, by using an exploratory approach. The subjects of the research are the policy holders in colleges, which include elements of the leaders and policy holders of information technology and college information systems. The object of research consists of various forms of digital strategies, ways of working, steps in higher education management in addressing the digital era. Data Collection with non-test techniques using an open questionnaire. Data collection is also done by documentation and observation. The research locations were at the Sriwijaya State Buddhist College in Tangerang Banten, Raden Wijaya State Buddhist College, Syailendra Buddhist College, Dharma Widya Buddhist College, and Kertarajasa Buddhist College. Data analysis was performed using the Miles and Huberman model. The results of the study stated that the digital technology planning of Buddhist Religious College in Indonesia is in the Strategic Plan (Renstra), Master Plan for Development (RIP), Work Program, ICT Blueprint, and contained in the Vision, Mission, and Strategy of the college. Barriers to Buddhist Religious College in implementing digital technology-based services are: 1) Low internet connections and bandwidth, 2) Digital and online-based libraries have not been implemented, 3) Information systems have not been integrated, 4) Technology infrastructure is less reliable, 5) Budget constraints in technologyical development, 6) Budget constraints for Information Technology Human Resources Salary, 7) Lack of Information Technology Human Resources, 8) Low Human Resources digital literacy competence, and 9) No follow-up on technological cooperation undertaken. The digital strategy of Buddhist Religious College in Indonesia consists of: 1) Increasing internet bandwidth, 2) Procurement of Digital Libraries, 3) Making ICT Blueprints, 4) Increasing technology development budgets, 5) Recruitment of Information Technology Human Resources, 6) Organizing seminars, workshops, and training in digital literacy competencies, and 7) Redefining technology cooperation. Permasalahan penelitian ini adalah bagaimanakah strategi digital Perguruan Tinggi Keagamaan Buddha (PTKB) di Indonesia. Fokus penelitian diarahkan pada strategi digital PTKB di Indonesia. Tujuan penelitian untuk mendeskripsikan strategi digital PTKB di Indonesia. Jenis penelitian ini adalah kualitatif dengan pendekatan eksploratif. Subjek penelitian adalah para pemegang kebijakan pada perguruan tinggi, yang meliputi unsur pimpinan serta pemegang kebijakan teknologi informasi dan sistem informasi perguruan tinggi. Objek penelitian terdiri dari berbagai bentuk strategi digital, cara kerja, langkah-langkah manajemen perguruan tinggi dalam menyikapi era digital. Pengumpulan data dengan teknik nontes menggunakan kuesioner terbuka. Pengumpulan data juga dilakukan dengan dokumentasi dan observasi. Lokasi penelitian yaitu pada Sekolah Tinggi Agama Buddha Negeri Sriwijaya Tangerang Banten, Sekolah Tinggi Agama Buddha Negeri Raden Wijaya, Sekolah Tinggi Agama Buddha Syailendra, Sekolah Tinggi Agama Buddha Dharma Widya, serta Sekolah Tinggi Agama Buddha Kertarajasa. Analisis data dilakukan dengan model Miles and Huberman. Hasil penelitian menyatakan perencanaan teknologi digital PTKB di Indonesia tertuang dalam Rencana Strategis (Renstra), Rencana Induk Pengembangan (RIP), Program Kerja, ICT Blueprint, dan tertuang dalam visi, misi, serta strategi perguruan tinggi. Hambatan PTKB dalam mengimplementasi pelayanan berbasis teknologi digital adalah: (1) koneksi dan bandwith internet rendah, (2) perpustakaan berbasis digital dan online belum terimplementasi, (3) sistem informasi belum terintegrasi, (4) infrastruktur teknologi kurang handal, (5) keterbatasan anggaran dalam pengembangan teknologi, (6) keterbatasan anggaran untuk gaji sumber daya manusia teknologi informasi, (7) kekurangan sumber daya manusia teknologi informasi, (8) kompetensi literasi digital sumber daya manusia rendah, dan (9) tidak adanya tindak lanjut kerja sama teknologi yang dilakukan. Strategi digital PTKB di Indonesia terdiri dari: (1) peningkatan bandwith internet, (2) pengadaan digital library, (3) membuat ICT blueprint, (4) peningkatan anggaran pengembangan teknologi, (5) rekrutmen sumber daya manusia teknologi informasi, (6) mengadakan seminar, workshop, dan pelatihan kompetensi literasi digital, dan (7) pendefinisian ulang kerja sama teknologi yang dilakukan.